Discrepancy Between Forceps Biopsy and Resection in Colorectal Polyps: A 1686 Paired Screening-Therapeutic Colonoscopic Finding [Corrigendum] - Jiang Y; Wang J; Chen Y; Sun H; Dong Z; Xu S (Therapeutics and Clinical Risk Management, 2022)
Jiang Y, Wang J, Chen Y, Sun H, Dong Z, Xu S. Ther Clin Risk Manag. 2022;18:561–569. The authors have advised that the Funding statement was missed from page 568 of the published paper. The funding statement should read as follows. Funding This study was funded by Shanghai Shenkang Hospital Development Center (grant number SHDC12016109) and Shanghai Municipal Health Commission (grant number 202040079). The authors apologize for this error.